Analisis Blue Ocean Strategy pada BMT Dana Mentari Muhammdiyah: Inovasi Dalam Pelayanan Keuangan Syariah - Yanuar Jidan; Anzil Farun Nisa; Devina Sabila Rahma; Yoiz Shofwa Shafrani (CV. KAMPUS AKADEMIK PUBLISING, 2025)
This studies pastimes to analyze the effectiveness of imposing the Blue Ocean approach at BMT Dana Mentari Muhammadiyah in improving the innovation of sharia economic services. This strategy is used to create new, unexplored areas, specially in the competitive microfinance zone. With a descriptive qualitative technique, data were gathered through interviews, observations, and documentation. The studies outcomes display that BMT Dana Mentari successfully developed a differentiation strategy through Sharia product innovations such as qurban savings, education savings, and mudharabah financing, as well as a humanistic and da'wah-based door-to-door marketing approach. The implementation of digital technology also strengthens the reach and efficiency of services. This strategy has proven effective in increasing member loyalty, expanding financial inclusion, and making significant contributions to the improvement of growth strategies for other Islamic microfinance institutions in Indonesia